2014
DOI: 10.1039/c4cp01827c
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the band gap of germanane nanoribbons for quantum well devices

Abstract: The effective modulation of the band gaps in nanostructures is of both fundamental and technological interest because a tunable band gap gives great flexibility in the design and optimization of nanodevices. Using density functional theory calculations, we have shown that germanane nanoribbons of various widths or under various strains can provide rich band gaps. Width- and strain-induced changes in the band gaps of germanane nanoribbons result from a reduction in quantum confinement with width and the weakeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Also, an additional strain can be easily applied to bilayer heterosystems by mechanical loading or a lattice mismatch on a substrate . Thus, it is necessary to investigate the strain effect on the functionalized Sc 2 C heterostructures because it is an important factor in determining the electronic properties of systems like other diverse low-dimensional materials. ,− When the heterostructures are influenced by the equibiaxial strain, type-III heterojunction is still preserved in the F/OH and O/OH systems (Figure S3, Supporting Information). On the other hand, it is notable that both of the F/O systems with different heterojunction types became type-II heterostructures by the biaxial strain effect (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, an additional strain can be easily applied to bilayer heterosystems by mechanical loading or a lattice mismatch on a substrate . Thus, it is necessary to investigate the strain effect on the functionalized Sc 2 C heterostructures because it is an important factor in determining the electronic properties of systems like other diverse low-dimensional materials. ,− When the heterostructures are influenced by the equibiaxial strain, type-III heterojunction is still preserved in the F/OH and O/OH systems (Figure S3, Supporting Information). On the other hand, it is notable that both of the F/O systems with different heterojunction types became type-II heterostructures by the biaxial strain effect (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The 2D germanane can be tailored into a narrowed ribbon structure which could offer a tunable band gap for various applications. 35 The germanane nanoribbons (GeNRs) can be classied into zigzag-and armchair-GeNRs according to their edge morphology. Following the previous convention, 60 the width of GeNRs are dened by parameter N: for zGeNRs, N denotes the number of zigzag carbon chains along the nanoribbon axis; for aGeNRs, N denotes the number of Ge-Ge dimers Fig.…”
Section: Germanane Nanoribbonsmentioning
confidence: 99%
“…11,12,[31][32][33][34] Investigations on the optical and transport properties, and the inuence of the defects of germanane-based nanomaterials are still rare. [35][36][37] In analogy to the case of graphane, the presence of hydrogen vacancies in the 2D germanane is expected to induce magnetization by unbinding the dangling p z orbital. 38 Recent advances in graphane and silicane have inspired us that cutting the 2D materials into narrowed ribbon could modulate the electronic structure, electronic transport, optical and magnetic properties of zigzag-and armchair-germanane nanoribbons (zGeNRs and aGeNRs).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37] In contrast, the research studies related to the electronic and transport properties of Ge-based nanomaterials, in particular for the chemically functionalized nanostructures, are still lacking. [38][39][40][41][42][43] It is crucial to explore the electronic transport properties of various functionalized germanane-based nanomaterials, which could facilitate the realization of spintronic applications in Ge-based 2D materials. [44][45][46] In this article, we have shown that O-germanene-H is a ferromagnetic metal with a spin efficiency of about 15%, which can be used as a spin-filter nanodevice.…”
Section: Introductionmentioning
confidence: 99%